2022
DOI: 10.1186/s40885-021-00186-y
|View full text |Cite
|
Sign up to set email alerts
|

Role of strain echocardiography in patients with hypertension

Abstract: Hypertension is a well-recognized risk factor for the development of cardiovascular disease, and the early detection of cardiac changes from hypertension can allow reversing these. Hypertensive heart diseases (HHD) refer to the complex and diverse change of the cardiac structure and function secondary to hypertension. Although conventional echocardiography is the most common imaging modality in detecting HHD, it cannot detect subtle changes of cardiac structure in subclinical states. Because strain echocardiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 79 publications
0
13
0
3
Order By: Relevance
“…GLS was lower among RH, although LVEF was preserved and similar between CH and RH groups. Thus, just as STE has been pointed as an early marker of myocardial damage, 35 even before any significant change in LVEF, we can assume that decreases in S‐LAr and S‐LAc may represent early evidence of HTN‐induced LA injury.…”
Section: Discussionmentioning
confidence: 90%
“…GLS was lower among RH, although LVEF was preserved and similar between CH and RH groups. Thus, just as STE has been pointed as an early marker of myocardial damage, 35 even before any significant change in LVEF, we can assume that decreases in S‐LAr and S‐LAc may represent early evidence of HTN‐induced LA injury.…”
Section: Discussionmentioning
confidence: 90%
“…Speckle tracking echocardiography with myocardial strain and strain rate is a more sensitive method to detect initial changes in the heart and can identify subtle adaptive changes in LV contractile mechanics in hypertensive patients without symptoms or signs of heart failure and with normal contractile function. 50 , 51 Myocardial strain and strain rate are also more sensitive to early and subtle changes in rodent cardiac function. 52 In this study, although conventional echocardiography did not show any difference between c‐MYPT2 −/− and MYPT2 +/+ mice at baseline, speckle tracking echocardiography showed that radial and longitudinal strain and strain rate were higher in c‐MYPT2 −/− mice than in MYPT2 +/+ mice.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, a systematic review showed that PLWH are at an increased risk of developing hypertension, with those on ART having a higher prevalence due to increasing age, BMI, and chronic inflammation ( 28 ). This is particularly concerning as hypertension is among the most significant risk factors for CVD, potentially leading to cardiac impairment and reduced myocardial strain ( 29 ). In our study, we observed that the impact of hypertension on myocardial function was noticeable even in a relatively young age, highlighting the importance of hypertension management in PLWH.…”
Section: Discussionmentioning
confidence: 99%